Mathematical Representation of MTs Students in HOTS-based Mathematical Problem Solving - Damayanti, Hanifah; Susiswo, Susiswo; Sulandra, I Made (Universitas Suryakancana, 2025)
This research is a descriptive qualitative research that aims to describe students’ mathematical representations in solving HOTS-based mathematical problems. This research was conducted at MTs Putri Al-Huda, Malang City. The subjects of this study were 2 grade VIII students selected based on high and medium abilities. Written tests and interview guidelines were the instruments in this study. The data analysis technique in this study used the Miles and Huberman method, namely data reduction, data presentation, and conclusion. The research results show that high-ability subjects produced verbal mathematical representations at the stage of understanding the problem and checking again, generate symbolic representations at the planning stages, implementing the plan, and checking again. Meanwhile, subjects with medium abilities produced verbal representations at the stage of understanding the problem, symbolic representations at the stage of making and implementing plans. Subjects with medium abilities did not produce any representations at the stage of checking again.